The Portuguese residential real estate market: An evaluation of the last decade - Tavares, Fernando Oliveira (2017)
his article presents an integrated vision of the context of the residential real estate market in Portugal. It analyses the evolution of several macroeconomic indicators during the last decade. The article is complemented with the analysis of the house prices, where an evaluation of average prices of apartments in Portugal according to different typologies and regions have been done. Regarding the market environment, several indicators are assessed, such as the evolution of interest rates, the evolution of households’ credit, the consumption and construction confidence indexes and the evolution of foreign direct investment in housing. The conclusion is that after a booming period, the future of the real estate market is somehow worrying.